Antioxidant Activity of Aloe vera and Prediction of Interaction Mechanisms on ROS1 Kinase and Collagenase Receptorsco - Atun, Sri; Aznam, Nurfina; Arianingrum, Retno; Azeeza, Sabira Nurul; Sangal, Aditi (Universitas Jenderal Soedirman, 2024)
The Aloe vera plant has been widely used as a food ingredient, medicine and cosmetics. This research aims to test the gel and ethanol extract of Aloe vera leaves as an antioxidant and absorber of UV light in vitro, as well as predicting the interaction mechanism for ROS1 kinase and collagenase receptors in silico.The antioxidant activity test method was carried out in vitro using DPPH (1,1-Diphenyl-2-Picrylhydrazyl-Hydrazine) reagent. Activity as a UV light absorber is carried out by calculating the sun protected factor (SPF) value. The antiaging activity test was carried out by predicting the interaction mechanism of the ROS1 kinase and collagenase receptors in silico using several phenolic compounds that have been found in Aloe vera. The total phenolic content of Aloe vera ethanol extract was 379.136 ± 0.34 GAE/g sample, while that of Aloe vera gel was 0.0619 ± 0.04 GAE/g sample. Aloe vera ethanol extract showed moderate antioxidant activity with an IC50 of 101.9 µg/mL, and is able to absorb UV light at concentrations of 0.05% and 0.1% with ultra protection criteria. Several phenolic compounds found in Aloe vera plants showed high binding energy to ROS1 kinase and collagenase receptors. Isoquercitrin showed the highest binding energy to the ROS1 kinase receptor, while isovitexin showed the highest binding energy to the collagenase receptor. The conclusion of this research showed that Aloe vera leaves contain compounds that have potential as antioxidants and antiaging. Keywords: Aloe vera, antioxidant, antiaging, ROS1 kinase, collagenase